ACE2 and SCARF expression in human dorsal root ganglion nociceptors: implications for SARS-CoV-2 virus neurological effects. Issue 11 (November 2020) - Shiers, Stephanie; Ray, Pradipta R.; Wangzhou, Andi; Sankaranarayanan, Ishwarya; Tatsui, Claudio Esteves; Rhines, Laurence D.; Li, Yan; Uhelski, Megan L.; Dougherty, Patrick M.; Price, Theodore J.
Abstract : Abstract: SARS-CoV-2 has created a global crisis. COVID-19, the disease caused by the virus, is characterized by pneumonia, respiratory distress, and hypercoagulation and can be fatal. An early sign of infection is loss of smell, taste, and chemesthesis—loss of chemical sensation. Other neurological effects of the disease have been described, but not explained. It is now apparent that many of these neurological effects (for instance joint pain and headache) can persist for at least months after infection, suggesting a sensory neuronal involvement in persistent disease. We show that human dorsal root ganglion (DRG) neurons express the SARS-CoV-2 receptor, angiotensin-converting enzyme 2 at the RNA and protein level. We also demonstrate that SARS-CoV-2 and coronavirus-associated factors and receptors are broadly expressed in human DRG at the lumbar and thoracic level as assessed by bulk RNA sequencing. ACE2 mRNA is expressed by a subset of nociceptors that express MRGPRD mRNA, suggesting that SARS-CoV-2 may gain access to the nervous system through entry into neurons that form free nerve endings at the outermost layers of skin and luminal organs. Therefore, DRG sensory neurons are a potential target for SARS-CoV-2 invasion of the peripheral nervous system, and viral infection of human nociceptors may cause some of the persistent neurological effects seen in COVID-19. Abstract : Supplemental Digital Content is Available in the Text.